2012
DOI: 10.1088/0957-4484/23/14/145201
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and resistive switching characteristics of high compact Ga-doped ZnO nanorod thin film devices

Abstract: This study investigates the resistive switching behavior of Ga-doped ZnO (GZO) nanorod thin films with various Ga/Zn molar ratios. Vertically well-aligned and uniform GZO nanorod thin films were successfully grown on Au/Ti/SiO(2)/p-Si substrates using an aqueous solution method. X-ray diffraction (XRD) results indicate that GZO nanorods have [0001] highly preferred orientation. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations show the formation of highly ordered and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…4. After the GZO nanorods growth, the defects or oxygen vacancies exist on the surface of each nanorod [15], [18], [25]. In other words, most oxygen vacancies exist at the location of the grain boundaries in the GZO nanorod film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4. After the GZO nanorods growth, the defects or oxygen vacancies exist on the surface of each nanorod [15], [18], [25]. In other words, most oxygen vacancies exist at the location of the grain boundaries in the GZO nanorod film.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the ZnO-based nanorods with transparent oxide electrode would produce good transparent RS memory if we can eliminate the existing holes or gaps between each nanorod. Our previous study reported that the well-aligned and extremely dense ZnO nanorods can be grown by doping Ga ions in ZnO aqueous synthesis during fabrication [18]. Those compact nanorods are due to the Ga dopants will change the interfacial energy between the ZnO seeding layer and nanorods during the nucleation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining favorable endurance properties is one of the major challenges for ZnO-based T-RRAM [7][8][9][10]. It has been suggested that the memory window should achieve the requirement of at least one order of magnitude to allow for small and highly efficient sense amplifiers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The doping method has already been adopted to optimize the switching performance of ZnO, including Mn, Co, Cu and Ga [15,16,18-20], but the switching properties were not as optimized as for practical applications. Very few studies of the electric conduction mechanism for Ti-doped ZnO films have been reported [21-23].…”
Section: Introductionmentioning
confidence: 99%